Non-performing assets (NPAs) and its impact on bank performance -with Special reference to ICIC Banks (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
India’s banking sector, especially public sector banks, has historically struggled with rising NPAs due to weak credit appraisal systems, economic slowdown, and corporate defaults. Non-performing assets (NPAs) pose a critical challenge to banking stability and economic growth, particularly in emerging economies like India. Non-Performing Assets (NPAs) are loans or advances for which the principal or interest payment remains overdue for a period of 90 days or more. NPAs are a critical indicator of the health of a banking system, reflecting the quality of a bank’s assets. High levels of NPAs can constrain a bank’s profitability, liquidity, and ability to lend, thereby affecting overall financial stability. This paper aims to analyze the critical issue of Non-Performing Assets (NPAs) in the Indian banking sector, with a specific focus on ICICI Bank. It seeks to understand the causes for the surge in NPAs, particularly after 2013, and to empirically examine their impact on the bank's profitability, operational efficiency, and shareholder value.